ORGANOLEPTIC VALUES AND NUTRITION CONTENT FROM NONI LEAVES (Morinda citrifolia) SILAGE FERMENTED BY DIFFERENT INOCULUM - N.D.E.A.D.P.S.M., Asmara; Mudita, I M.; Mariani, N. P. (Jurnal Peternakan Tropika; Vol 8 No 3 (2020): Vol. 8 No. 3 Tahun 2020; September - December, 2020)
This study aims to determine the organoleptic value and nutrient content of noni leaves (Morinda citrifolia) silage that is fermented by different inoculums. The study was conducted from June to September 2019 at the Faculty of Animal Husbandry Research Station and the Laboratory of Nutrition and Animal Feed of the Faculty of Animal Husbandry, Udayana University. The design used in this study was a complete random design (CRD) consisting of five treatments, namely the silage of noni leaves without inoculum as a control (A), noni leaves fermented inoculum combination of microorganism/ Effective Microorganism-4/EM-4 (B), noni leaves fermented inoculum yeast Saccaromyces serevisiae (C), noni leaves fermented inoculum bacterial Bacillus sp strain BT 3 CL (D), and noni leaves fermented inoculum bacterial Bacillus subtilis strain BR 2 CL (E), each treatment was repeated three times. The variables observed were organoleptic values ??including fungi, texture, color and silage odor, while the nutrient content were: dry matter (BK), moisture content, crude protein (PK), crude fiber (SK), crude fat (LK), ash and organ?k material (BO), The results of studies of noni leaves fermented using bacterial inoculums (Treatment D and E) produce no slime fungi. Treatment D produced the best colored s?lase, treatment E produced silage with the best scent /odor, and the use of a yeast inoculum (C treatment) produced the best texture, the highest quality organic material (P<0,05) and the lowest crude fiber (P<0,05). The use of a combination inoculum (EM-4/Treatment B) produced silage with the highest crude protein (P<0,05). Based on the results of the study it was concluded that the use of bacterial inoculums (Treatment D and E) produced the best organoleptic values. The use of yeast inoculum (Treatment C) and combination inoculum (EM-4 Treatment B) produce the best nutrient content. Keywords : inoculum, noni leaves, nutrient content, organoleptic, silage